Implementasi Pengajaran Tentang Keteladanan Yesus Berdasarkan Injil Yohanes 13:1-20 Bagi Tenaga Pendidik SMP Sungai Kehidupan - Febrianti, Melati; Istinatun, Hestyn Natal; Parulian, Tamba; Latupeirissa, Jacobus (Basilius Eirene Press, 2022)
The example of Jesus is one of the concepts in the Bible that seems simple, but is difficult for Christians to do. The example of Jesus has difficulties due to the lack of a correct understanding of the example of Jesus. The role of Jesus' example in Christian life does not seem to have any impact, so that it is assumed that Jesus' exemplary act is only a social activity. The Lord Jesus gave a good example in the Gospel of John 13:1-20 about giving an attitude of living by example. Therefore, this study aims to determine the level of implementation of teaching about the example of Jesus based on the Gospel of John 13:1-20 for educators at Sungai Hidup Nanga Pinoh Junior High School, West Kalimantan as well as the most dominant dimension determining the implementation of teaching about the example of Jesus based on the Gospel of John 13. :1-20 for educators at Sungai Hidup Nanga Pinoh Middle School, West Kalimantan. This study uses quantitative methods, data obtained from library sources and distributed questionnaires. The results show that the level of implementation of teaching about the example of Jesus based on the Gospel of John 13:1-20 for Educators at Sungai Hidup Nanga Pinoh Middle School, West Kalimantan is in the medium category. The more dominant dimension that determines the level of implementation of the teaching about the Example of Jesus based on the Gospel of John 13:1-20 for Educators at Sungai Hidup Nanga Pinoh Junior High School, West Kalimantan is exemplary to serve one another.